Entry Strategies of Partnerships versus Conventional Firms. - Moretto, Michele; Rossini, Gianpaolo (Southern Economic Journal, 2008)
From 1997 to 2001 the number of nonemployer businesses, mostly partnerships, grew faster than conventional firms in the United States, a country with the mildest asymmetries between the two types of enterprises with respect to taxation, administrative entry barriers, and other institutional aspects. Partnerships are smaller than conventional firms, and their different speeds of net entry could be the result of internal organization that makes them swifter and better equipped to be fast-growing industries. In a continuous-time stochastic environment with sunk costs, we model entry as a growth option. Partnerships and conventional firms display specific patterns in terms of output price and size in that they appear to react in diverse fashions to market uncertainty. In most cases, the partnership is less risky and better suited to enter under conditions of high volatility, as between 1997 and 2001 in the United States.